2007
DOI: 10.1021/jp066727c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquids on the Aggregation Behavior of PEO-PPO-PEO Block Copolymers in Aqueous Solution

Abstract: Effect of 1-butyl-3-methyl-imidazolium bromide (BmimBr) on the aggregation behavior of PEO-PPO-PEO Pluronic P104 aqueous solution was studied by Fourier transform infrared (FTIR) spectroscopy, freeze fracture transmission electron microscopy (FF-TEM), dynamic light scattering (DLS), and NMR spectroscopy. When the BmimBr concentration was below 1.232 mol/L, the critical micelle temperature (CMT) of Pluronic P104 remained constant, while the size of micelles increased with increasing the BmimBr concentration; ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 34 publications
4
73
0
1
Order By: Relevance
“…As far as IL-induced changes in micellar size are concerned, it is reported that addition of [bmim][Br] to aqueous solution of a block copolymer, PEO-PPO-PEO Pluronic P104, resulted in a dramatic increase in the effective diameter of the micelles formed by this nonionic copolymer [84]. However, our earlier reports indicate a decrease in the size of micellar aggregates upon addition of 2 wt% [bmim] [BF 4 ] to aqueous nonionic TX100 [52]; the addition of the same amount of this IL to aqueous anionic SDS resulted in a dramatic increase in micellar size [54].…”
Section: Size Of Micellar Aggregates From Dynamic Light Scatteringmentioning
confidence: 99%
“…As far as IL-induced changes in micellar size are concerned, it is reported that addition of [bmim][Br] to aqueous solution of a block copolymer, PEO-PPO-PEO Pluronic P104, resulted in a dramatic increase in the effective diameter of the micelles formed by this nonionic copolymer [84]. However, our earlier reports indicate a decrease in the size of micellar aggregates upon addition of 2 wt% [bmim] [BF 4 ] to aqueous nonionic TX100 [52]; the addition of the same amount of this IL to aqueous anionic SDS resulted in a dramatic increase in micellar size [54].…”
Section: Size Of Micellar Aggregates From Dynamic Light Scatteringmentioning
confidence: 99%
“…Micellar solutions show excellent properties in chemical reactions [1], drug delivery [2,3], and the synthesis of nanomaterials [4,5]. The study of the properties of micellar solutions has been an interesting topic for many years [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that ILs acted as a metal salt at low concentrations and participated in the micellar phase with increasing [C 4 mim] [PF 6 ] which led to a considerable decrease in the microfluidity of SDS micelles (Behera & Pandey, 2007a, b). ILs also influence the aggregation behavior of Pluronic polymers (Dey et al, 2009;Zheng et al, 2007). Zheng et al The formation of liquid crystal in ILs was firstly reported by Evans and co-workers (Evans et al, 1983a) in 1983, which was formed by β,  γ-distearoylphosphotidylcholine (DSPC) in EAN.…”
Section: Effects Of Ionic Liquids On the Formation Of Supramolecular mentioning
confidence: 98%